Importance of human capital, field knowledge and experience to improve pest locust management - Gay, Pierre-Emmanuel; Trumper, Eduardo Victor; Lecoq, Michel; Piou, Cyril (2021)
BACKGROUND: A poorly organised risk management system may dysfunction when used. The consequences can be dramatic for those supposed to be protected. Since the 1960s, preventive control strategies, with field officers as living memory, have been developed to monitor locusts. Preserving their experience of past plagues is consequently essential. Wrong use of their knowledge can disrupt the whole management chain. We explored these conditions using a multi-agent model representing a preventive system. We simulated how the field teams' tendency to repeatedly visit past outbreak areas (hotspots) by allocating them an attraction weight can help in preventing plagues. RESULTS: When field teams' attention remained constant over time, there was dramatic decrease in the number of plagues, with increasing interest in hotspots, as long as interest was less than 2.5 times more than elsewhere. When the field teams were only attentive during recession times, plagues were better controlled using a low weight for hotspots. The spatial structure of hotspot distribution had an effect: the more frequent and the bigger the hotspots, the lower the optimal hotspot weighting needed to reduce plagues. CONCLUSION: Orienting surveys towards hotspots particularly during recession times reduces plagues. The spatial structure of locust habitats may influence the way they are managed. Habitats located outside the multiple hotspots of species such as the desert locust should be visited more frequently than those with only one hotspot, such as the South American locust. The decline/loss of the field officers' experience highlights the need to save, capitalise and disseminate this knowledge.